Corrigendum to "Do human sinoatrial node cells have t-tubules?" [Transl. Res. Anat. 25C (2021) 100131] - Maria A. Petkova; Halina Dobrzynski (Elsevier, 2022)
Background and purpose: Every heartbeat is generated by spontaneously depolarizing specialised nodal cells that make up the sinoatrial node (SN). The SN's unique properties depend on two complex mechanisms - the membrane-voltage and the Ca2+ clocks, regulated by strictly defined expression of ion channels, connexins and Ca2+-handling proteins. In the working myocardium these proteins are accumulated in specialised membrane structures- the transverse tubules (t-tubules). It is well known that small mammals do not exhibit t-tubules in their atrium, but such structures are observed in the atria of bigger mammals such as sheep. No information on t-tubules in the human SN is present yet. The aim of our study was to determine if t-tubules are present in the human SN, as well as surrounding atrial myocardium. Basic procedures: Dystrophin (cytoplasmic protein connecting the muscle fibres to the surrounding extracellular membrane), Na+-Ca2+ exchanger (NCX1), sarcoplasmic-endoplasmic reticulum calcium adenosine triphosphatase (SERCA2a), α-actinin, and ryanodine receptor 2 (RyR2) were investigated. Main findings and principal conclusions: Staining with wheat germ agglutinin (WGA, specific marker of t-tubules) demonstrated that human RA cells contain t-tubules, but these structures are very sparse in the SN. Experiments in single nodal cells from rat and mouse showed no expression of t-tubular network, but striated pattern of expression of RyR2 was obtained similar to the human sections, suggesting its manner of organization is dependent on α-actinin colocalization.